Rancang Bangun Aplikasi Transaksi Elektronik Ritel Pupuk Dengan Metode Electronic Data Interchange (EDI) - Nelly Oktavia Adiwijaya; Nurul Istiana M; Slamin . (JURNAL NASIONAL TEKNIK ELEKTRO, 2015)
Fertilizer distribution from distributor to agents, are required to be responsive in addressing the demand for fertilizers. Distributors are also required to be able to manage inventory in the warehouse, to avoid overstocking of fertilizer. Design and implementation of  a fertilizer retail electronic commerce applications using electronic data interchange (EDI) method is applied in this study. The system is built to help distributors to control the existence of the stock of fertilizer so no excess stock. In addition, the use of EDI can provide information quickly (real-time) without having to go directly to the warehouse locations.Keywords : Application, Retail,  Electronic data interchange (EDI)